SUSTAINABLE DEVELOPMENT IN THE CIRCUMPOLAR NORTH - From Tana, Norway to Oktemtsy, Yakutia, Russia - Gjertsen, Tor; Halseth, Greg (Septentrio Conference Series, 2014)
The Gargia Conferences for Local and Regional Development (2004-14)Tor Gjertsen and Greg Halseth (eds.) UArctic Thematic Network on Local and Regional DevelopmentUiT/The Arctic University of Norway, University of Northern British Columbia2015